Zona de negocios y fomento industrial de la Sabana Centro 2030: Plan parcial alianza Agrozipa (2017)
A partial plan with a polygon of action of 12 hectares which was developed by different axis starting with the industrial hub then administrative hub, commercial, logistics and finally recreational shaft to strengthen the process of regional integration, which means economic growth for competitiveness in the province Savannah Center was designed.